2009
DOI: 10.1177/1358863x09104658
|View full text |Cite
|
Sign up to set email alerts
|

Lower-leg symptoms in peripheral arterial disease are associated with anxiety, depression, and anhedonia

Abstract: Patients with peripheral arterial disease (PAD) report diverse clinical manifestations that are not always consistent with classic intermittent claudication. We examined the degree to which atypical exertional leg symptoms, intermittent claudication, and exertional leg symptoms that begin at rest were associated with mood states such as anxiety, depressive symptoms, and anhedonia (i.e. lack of positive affect). A cohort of consecutive PAD patients (n = 628) from the Erasmus Medical Center, Rotterdam, The Nethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 34 publications
5
53
0
4
Order By: Relevance
“…Cross-sectional studies in patients with peripheral arterial disease have shown that decreased lower extremity functioning by 6-minute walk test20,21 and increased self-reported rest pain24 are associated with depressive symptoms, although the directionality of these associations is not clear. A prospective study showed an association between baseline diabetic peripheral neuropathy severity and depressive symptoms 18 months later, and this relationship was partially mediated by the symptoms of pain and unsteadiness 25…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional studies in patients with peripheral arterial disease have shown that decreased lower extremity functioning by 6-minute walk test20,21 and increased self-reported rest pain24 are associated with depressive symptoms, although the directionality of these associations is not clear. A prospective study showed an association between baseline diabetic peripheral neuropathy severity and depressive symptoms 18 months later, and this relationship was partially mediated by the symptoms of pain and unsteadiness 25…”
Section: Discussionmentioning
confidence: 99%
“…Criterion scores of ≥ 8 for the depression subscale denote clinically relevant symptoms of depression. 2627 …”
Section: Methodsmentioning
confidence: 99%
“…Patients with PAD have markedly reduced health- related quality of life and higher prevalence of depression which is largely related to leg symptoms 23,24. Diminished physical activity in daily life predicts higher overall mortality in PAD 25,26.…”
Section: Functional Disability In Padmentioning
confidence: 99%